Is there a place for nutrition-sensitive agriculture? - Wambugu, Florence; Obukosia, Silas; Gaffney, Jim; Kamanga, Daniel; Che, Ping; Albertsen, Marc C.; Zhao, Zuo-Yu; Ragland, Lonnetta; Yeye, Mary; Kimani, Esther; Aba, Daniel; Gidado, Rose; et al. (Proceedings of the Nutrition Society, 2015)
The focus of the review paper is to discuss how biotechnological innovations are opening new frontiers to mitigate nutrition in key agricultural crops with potential for large-scale health impact to people in Africa. The general objective of the Africa Biofortified Sorghum (ABS) project is to develop and deploy sorghum with enhanced pro-vitamin A to farmers and end-users in Africa to alleviate vitamin A-related micronutrient deficiency diseases. To achieve this objective the project technology development team has developed several promising high pro-vitamin A sorghum events. ABS 203 events are so far the most advanced and well-characterised lead events with about 12 μg β-carotene/g tissue which would supply about 40–50 % of the daily recommended vitamin A at harvest. Through gene expression optimisation other events with higher amounts of pro-vitamin A, including ABS 214, ABS 235, ABS 239 with 25, 30–40, 40–50 μg β-carotene/g tissue, respectively, have been developed. ABS 239 would provide twice recommended pro-vitamin A at harvest, 50–90 % after 3 months storage and 13–45 % after 6 months storage for children. Preliminary results of introgression of ABS pro-vitamin A traits into local sorghum varieties in target countries Nigeria and Kenya show stable introgression of ABS vitamin A into local farmer-preferred sorghums varieties. ABS gene Intellectual Property Rights and Freedom to Operate have been donated for use royalty free for Africa. Prior to the focus on the current target countries, the project was implemented by fourteen institutions in Africa and the USA. For the next 5 years, the project will complete ABS product development, complete regulatory science data package and apply for product deregulation in target African countries.